Otimização dos parâmetros de fluxo e forças dinâmico-mecânicas em arcabouços de Poli(pcl-tmc)uretana cultivados com condrócitos em biorreator - Pedrini, Flavia Maria Morais (2019)
The growing advances in tissue engineering, the development of cell culture technologies associated with biocompatible and three-dimensional scaffolds have shown to be promising for the regeneration of tissues and organs. The meniscus is constitudet by a fibrocartilaginous tissue, partially vascularized, subjected to great mechanical stresses and when it is injured is removed partially or totally, leading to future joint complications. An unique prosthesis based on polyurethane is marketed, but it is not acessible due to its high cost. In view of this scenario, membranes were obtained by solvent evaporation and the scaffolds by the lyophilization process from a new polyurethane, Poly (Polycaprolactone-co-Trimethylene Carbonate) urethane (Poly (PCL-TMC) urethane). Scanning electron microscopy (SEM) showed the presence of interconnected pores in the three-dimensional structure of the material. The membranes and the scaffolds were submitted to cytocompatibility, proliferation and cell differentiation assays, respectively, by culturing mesenchymal stem cells (MSCs). In most assays, a dynamic and mechanical flow mode bioreactor was used at a rate of 0.4 mL/min with or not application of 1N and 2N compression force, whether or not subjected to differentiation. When forces were applied, the number of cells in the polyurethane scaffolds decreased over time due to polymer fatigue. From these results, the tests were performed only in dynamic flow mode at the rate of 0.4 mL / min. Laser confocal scanning microscopy (LCSM) analysis showed that the rate promoted cell growth and differentiation within the Poly (PCL-TMC) urethane scaffolds. This study demonstrated the applicability of the polymer as a cellular carrier in tissue engineering approaches for future application as a meniscal prosthesis.